THE ANALYSIS OF MARKETING COSTS: CASE OF ALQUEBY HOTEL - , ERNEST HIDAYAT ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Marketing is one of management function that contributes to the performance and goals of company. Therefore, management should take care of the efficiency and effectiveness in spending on marketing costs in order to achieve certain objective or optimum return in terms of financial outcomes. Since, most of the time managersâ expectations are not always met by the performance of company. Thus, this research aims to give analysis on marketing costs in the case of Alqueby Hotel as an object study. This study objectives are to investigate the influence of marketing costs to net income and roomâs occupancy percentage in the period of 10 months (August 2013 âMay 2014). This study uses the data analysis methods of qualitative descriptive analysis, which is data reduction, data display, conclusion drawing, and narrative analysis. Thus, it can a basis for the analysis of marketing costs toward net income and roomâs occupancy percentage.